ENT 530 Social Media Portfolio: Chocodaps / Nurul Aina Azlan - Azlan, Nurul Aina (2021)
This Social Media Portfolio was created to demonstrate how digital technology helps in online sales marketing. Chocodaps offers a wide range of chocolate goods in a variety of flavours. It identifies persons who crave sweets and chocolate for snacking. It has a reasonable pricing for all sorts of chocolate. It invites people of all ages, including children and adults, to taste our Chocodaps. Chocodaps' marketing approach focuses on the product's quality and pricing. It provides an inexpensive price for everyone, especially students, who desire excellent on-the-go snacks. Chocodaps are available in Ampang Jaya, Selangor, but we also offer a delivery service to homes, offices, and colleges, using cash on delivery and online banking as our primary payment methods. The management of Chocodaps consists by May Sarah. As agent, I also created a Facebook page in order to develop my business through the social media platform, and I learned how to post on Facebook for business products such as teasers, soft sales, and hard sales. This platform enables me to promote my product not only in my area but also in other states.